Beyond Formal Procedures: Cross-Factional Political Communication, Negotiation, and Consensus Building in Local Policy Formulation - Hendry Ch. Soselisa; Nur Aini Nahumarury; Ardy Gunawan Tomagola (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study examines cross-factional political communication in public policy formulation within the Central Maluku Regency DPRD using a political sociology perspective and qualitative methods. The findings reveal that formal and informal communication complement each other in facilitating negotiation, conflict resolution, and consensus-building throughout the policymaking process. Communication effectiveness is strengthened by integrated political networks, digital media adaptation, and political party coordination through ideological alignment, organizational discipline, and coalition-building. Deliberative negotiation and the integration of constituents’ aspirations further enhance policy legitimacy. These findings highlight the critical role of effective cross-factional communication in strengthening legislative performance, promoting inclusive governance, and improving public policy outcomes.